2017
DOI: 10.1177/0143034317714839
|View full text |Cite
|
Sign up to set email alerts
|

International approaches to school-based mental health: Intent of the Special Issue

Abstract: This article provides an overview of the special issue on international approaches to school-based mental health. It introduces the significance of the issues associated with mental health across the world and introduces the reader to the four articles highlighting different aspects of school-based mental health. Across these four articles, information about school-based mental health (SBMH) from the United States, Canada, Norway, Liberia, Chile, and Ireland are represented. The special issue concludes with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The number of institutions within 3 km from the school was obtained by Baidu map (a widely used guide application in China). These variables were included based on previous related studies …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of institutions within 3 km from the school was obtained by Baidu map (a widely used guide application in China). These variables were included based on previous related studies …”
Section: Methodsmentioning
confidence: 99%
“…16 School, considered as a second home of youths, may be associated with improved mental wellbeing via a sense of integration. 17 Mental health programs in school settings play a crucial role in prevention efforts, 18 and many studies have shown that school-based interventions were associated with improved mental well-being among youths. 19,20 However, the association between schoolprovided psychological resources and student mental health has been less studied and remains a topic of debate.…”
Section: Introductionmentioning
confidence: 99%
“…Besides families, schools represent the second social environment where children and adolescents spend a lot of their time, and on which a large part of their learning and development depends. Given the above, schools become the venue where early signs of mental health problems can be detected and where access to intervention can be provided promptly (9). This recognition has led to the rise of school-based mental health services, with the aims of promoting mental health awareness, as well as prevention and amelioration of students' mental health problems (10).…”
Section: Introductionmentioning
confidence: 99%